Tai-Chi und moderates aerobes Training vermindern die Symptome von Fibromyalgie-Patienten - Ammer, K. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2018)
Referat zur Arbeit von Wang C, Schmid CH, Fielding RA, Harvey WF, Kieran F Reid KF, Price LL, Driban JB, Kalish R, Rones R, McAlindon T. Effect of tai chi versus aerobic exercise for fibromyalgia: comparative effectiveness randomized controlled trial. BMJ 2018; 360: k851